Pyroptosis, a New Breakthrough in Cancer Treatment - Wu, Dengqiang; Wei, Changhong; Li, Yujie; Yang, Xuejia; Zhou, Sufang (Frontiers in Oncology, 2021)
The way of cell death can be roughly divided into two categories: cell necrosis and PCD( programmed cell death). Pyroptosis is a kind of PCD, its occurrence depends on the gsdermin protein family and it will produce inflammatory response. With constant research in recent years, more and more evidences show that pyroptosis is closely related to the occurrence and development of tumors. The treatment of tumors is a big problem worldwide. We focus on whether we can discover new potential tumor markers and new therapeutic targets from the mechanism. If we can understand the mechanism of pyroptosis and clear the relationship between pyroptosis and the development of tumors, this may provide a new reference for clinical cancer treatment.